STRATEGI PENGEMBANGAN PARIWISATA DI KABUPATEN PEMALANG - Dwimawanti, Ida Hayu; Suryaningsih, Margaretha; Rahman, Rafa’ Fazlur (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Development Strategy of Tourism Research in Pemalang a qualitative descriptive study. This study uses strategic planning so that explains the strategic issues in the development of tourism overall. The focus of this research is that tourism development strategy on research using a SWOT analysis as the main tool to analyze and measure the environment in order to produce a strategy that is used for the preparation of the planning process of tourism development. Informants in this study is from the Head of Culture and Tourism, Head of Product Development Tourism, Tourism Promotion Section Head, Chairman of the Regional Tourism Promotion Board, The Winner Hotel Manager, Deputy Manager attractions Zatobay, Community and Traders in Attractions Widuri. Process research begins analysis of the conditions tourism , the identification of external and internal environment that produces weaknesses, strengths, opportunities and threats. Furthermore, analyzing the strategies based on the identification of weaknesses, strengths, opportunities and threats in the SWOT analysis. After that produces strategy SO, WO, ST, and WT is then in the value of using a litmus test to determine alternative strategies. The highest value a strategic issue that can be applied to the conduct of tourism development in the district of Pemalang